Facility Layout Planning of Sheet Metal Working Industry Using Metaheuristics - Ludwika, Adinda Sekar; Shalehah, Mar’atus; Mohamad, Rakan Raihan Ali; Oktavia, Andiny Trie; Normasari, Nur Mayke Eka; Tho, Nguyen Huu; Rifai, Achmad Pratama (Spektrum Industri, 2024)
The design of facility layout in a production floor determines the level of effectiveness and efficiency of the production process. Errors in arranging the layout in the production floor can disrupt the continuity of the production process and prevent optimal results. Production activities that occur over a long period of time make any inaccuracies in layout planning result in significant losses. In companies with Job Shop production type, which is characterized by identical products and varied processes, the production flow changes with each product made. Based on these issues, this research aims to optimize the layout in a company engaged in sheet metal working industry using metaheuristic algorithms such as Simulated Annealing (SA), Large Neighborhood Search (LNS), Adaptive Large Neighborhood Search (ALNS), and Ant Colony Optimization (ACO). The best total distance results were obtained by the SA, LNS, and ALNS algorithms, with a total travelled distance of 897,171 meters and a facility arrangement of 7-5-6-4-3-2-1 or 1-2-3-4-6-5-7. Additionally, considering computation time, the SA algorithm is the best choice as it has the fastest computation time compared to other algorithms.